Wpływ rozwoju sektora bazowego na dochody ludności - studium przypadków - Goleń, Marek J. (The Influence of the Basis Sector Development on the Incomes of the Commune Population - Case Studies, 2006)
The article discusses the results of four commune case studies, where were realized developmental investments of the local basis sector. The main aim of the research is to identify an influence of investments in a basis sector of the local economy on incomes of population of a commune and also to try to estimate the scale of this influence. The research is an attempt of the practical verification of the theoretical model of the impact of these investments on incomes of local production factors. The research was carried out in 4 communes: Bukowina Tatrzańska, Garwolin, Tuczno and Żukowo where the new investments were located. The new investments were adequately: the ski center, the cosmetics factory, the chocolate factory and the ice-cream factory. The crucial impact of the investment on incomes of population of a commune was identified in the first and the second of the listed communes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 603-613